1996
DOI: 10.1136/bjsm.30.2.148
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of rock climbing injuries.

Abstract: (BrJt Sports Med 1996;30: 148-150)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 5 publications
3
48
0
Order By: Relevance
“…Fall-related injuries are comparatively uncommon, although often serious, and all climbers may incur them. Previous research has tended to focus upon the description of climbing injuries in specific groups5 8 or those presenting at medical facilities 9 10. The present study therefore extends the existing literature by examining the associations between a wide range of potential risk factors and injuries in a diverse sample of active rock climbers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fall-related injuries are comparatively uncommon, although often serious, and all climbers may incur them. Previous research has tended to focus upon the description of climbing injuries in specific groups5 8 or those presenting at medical facilities 9 10. The present study therefore extends the existing literature by examining the associations between a wide range of potential risk factors and injuries in a diverse sample of active rock climbers.…”
Section: Discussionmentioning
confidence: 99%
“…Of 19 climbers presenting to an urban accident and emergency (A&E) department over a year, 14 were injured at outdoor venues 9. Of the 19 climbers, 18 had been injured as the result of falls, and 12 had sustained fractures (4 of which were missed on initial attendance).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, our survey differs from previously published articles, where only specific groups of climbers such as young sport climbers [6], experienced rock climbers [4], or sportsmen performing only extreme sport climbing [12] were analyzed. Other studies exclu- sively reported data specific to selected climbing conditions, such as indoor climbing on artificial walls [3,13] or outdoor climbing [14], or to climbers who presented in a medical facility [15]. Also, the proportion of women incorporated in our study was greater than usual (31 % as compared with 9 % in [4]).…”
Section: Discussionmentioning
confidence: 75%
“…Two papers were studies of diagnostic accuracy (18,19). The remainder of the articles included seven reviews (10,13,(15)(16)(17)24,34), two case studies (8,9), eight comparative studies (12,14,22,23,27,28,30,31), and 10 noncomparative studies (2,3,11,20,21,25,26,29,32,33), of varying quality. The findings are presented below in three sections corresponding to the three research questions.…”
Section: Resultsmentioning
confidence: 99%